Brand ISIS: Interactions of the Tangible and Intangible Environments. Issue 4 (2nd October 2018) - Simons, Greg
Abstract : This article investigates how the infamous terrorist organization Islamic State (ISIS) uses branding and political marketing as means to increase their intangible value and assets in order to influence their tangible (operational) capacities. In order to investigate the logic of a terrorist organization as a political actor a perspective of political communication is applied as a means to understand more clearly the propaganda of the word and the propaganda of the deed. A systematic communication approach is used to raise awareness of the ISIS brand in order to differentiate the organization and to create a greater sense of credibility and authenticity in an increasingly crowded marketplace of terrorist organizations seeking for attention, support, and fear. Aspects of political marketing are used in order to create sets of relationships of attraction and avoidance with different target audiences. The 15 issues of the magazine Dabiq are examined and analyzed within this approach. However, intangible communication and tangible realities do affect each other. This is evident when there is a swing from military victories to military defeats, which impacts on the quality and quantity of communicational materials produced by ISIS.